Principles Audi Et Alteram Partem Compatibility in Litigation Process at State and Religious Court: Impact of Pandemic - Sekhar Chandra Pawana; Vincentius Patria Setyawan (Musamus Law Review, 2022)
The Covid-19 pandemic that surge around the world, caused adjustments in various ways, including in the law. The existence of regulations regarding e court strongly supports government programs in suppressing the rate of development of the Covid-19 virus, but on the other hand this development raises questions regarding the application of the principle of audi et alteram partem. This paper aims to present how the application of Principles Audi Et Alteram Partem Compatibility in Litigation Process in State and Religious Court in emergency situation. This study uses an normative method approach with descriptive analytical research specifications. This research seeks to illustrate the facts of the Audi et Alteram Partem Principle Compatibility in E-court anda E-Litigation.. Starting from this, there should be synchronization and uniformity of rules for all judicial processes, which should ideally be conducted electronically. From the results of the study, the implementation of the electronic trial shows the application of the principle of audy et alteram partem. All of this is in the interest of the justice-seeking community itself so that the trial process can better guarantee. It is found that even though the court process is conducted online, the principle of audi et alteram partem can be realized.